ACMT Position Statement: Preventing Cannabis Exposures in Children (2026) - Robert G. Hendrickson; Maryann Mazer-Amirshahi; Caitlin Bonney; Michele Burns; Diane P. Calello; Suzanne Doyon; Jeremy Hardin; Hannah Hays; Diane E. Hindman; Erica Liebelt; Michael J. Moss; Lewis Nelson; et al. (Journal of Medical Toxicology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

What ancient DNA reveals about the ubiquitous rockfish of the Pacific Coast of North America - Madonna L. Moss; Brittany Bingham; Raven Blankenship; Upuli DeSilva; Ryan Frome; Marie Capps; Joy Li; Erica Palmer; Krithivasan Sankaranarayanan; Brian M. Kemp (Archaeological and Anthropological Sciences, 2022)

Preface: Shallow lakes in a fast changing world - Meryem Beklioğlu; Mariana Meerhoff; Thomas Alexander Davidson; Kemal Ali Ger; Karl Havens; Brian Moss (Hydrobiologia, 2016)

Modelling Primary Producer Interaction and Composition: an Example of a UK Lowland River - Attila N. Lázár; Andrew J. Wade; Brian Moss (Environmental Modeling & Assessment, 2016)

Switchgrass (Panicum virgatum L) flag leaf transcriptomes reveal molecular signatures of leaf development, senescence, and mineral dynamics - Nathan A. Palmer; Teresa Donze-Reiner; David Horvath; Tiffany Heng-Moss; Brian Waters; Christian Tobias; Gautam Sarath (Functional & Integrative Genomics, 2015)

Comment: Cultural eutrophication of natural lakes in the United States is real and widespread - Val H. Smith; Walter K. Dodds; Karl E. Havens; Daniel R. Engstrom; Hans W. Paerl; Brian Moss; Gene E. Likens (Limnology and Oceanography, 2014)

Nitrogen, macrophytes, shallow lakes and nutrient limitation: resolution of a current controversy? - Brian Moss; Erik Jeppesen; Martin Søndergaard; Torben L. Lauridsen; Zhengwen Liu (Hydrobiologia, 2013)

Warmer climates boost cyanobacterial dominance in shallow lakes - Sarian Kosten; Vera L. M. Huszar; Eloy Bécares; Luciana S. Costa; Ellen van Donk; Lars‐Anders Hansson; Erik Jeppesen; Carla Kruk; Gissell Lacerot; Néstor Mazzeo; Luc De Meester; Brian Moss; et al. (Global Change Biology, 2012)
Dominance by cyanobacteria hampers human use of lakes and reservoirs worldwide. Previous studies indicate that excessive nutrient loading and warmer conditions promote dominance by cyanobacteria, but evidence from global scale field data has so far been scarce. Our analysis, based on a study of 143 lakes along a latitudinal transect ranging from subarctic Europe to southern South America, shows that although warmer climates do not result in higher overall phytoplankton biomass, the percentage of the total phytoplankton biovolume attributable to cyanobacteria increases steeply with temperature. Our results also reveal that the percent cyanobacteria is greater in lakes with high rates of light absorption. This points to a positive feedback because restriction of light availability is often a consequence of high phytoplankton biovolume, which in turn may be driven by nutrient loading. Our results indicate a synergistic effect of nutrients and climate. The implications are that in a future warmer climate, nutrient concentrations may have to be reduced substantially from present values in many lakes if cyanobacterial dominance is to be controlled.

Conservation of pond systems: a case study of intractability, Brown Moss, UK - Ratcha Chaichana; Rick Leah; Brian Moss (Hydrobiologia, 2011)

Increased ambient temperature alters the parental care behaviour and reproductive success of the three-spined stickleback (Gasterosteus aculeatus) - Kathryn Hopkins; Brian R. Moss; Andrew B. Gill (Environmental Biology of Fishes, 2011)

Preface - Mariana Meerhoff; Meryem Beklioglu; Romi Burks; Felipe García-Rodríguez; Néstor Mazzeo; Brian Moss (Hydrobiologia, 2010)

Birds as eutrophicating agents: a nutrient budget for a small lake in a protected area - Ratcha Chaichana; Rick Leah; Brian Moss (Hydrobiologia, 2010)

Local adaptation to higher temperatures reduces immigration success of genotypes from a warmer region in the water flea Daphnia - WENDY VAN DOORSLAER; JOOST VANOVERBEKE; CATHY DUVIVIER; SARAH ROUSSEAUX; MIEKE JANSEN; BASTIAAN JANSEN; HEIDRUN FEUCHTMAYR; DAVID ATKINSON; BRIAN MOSS; ROBBY STOKS; LUC DE MEESTER (Global Change Biology, 2009)
There is growing awareness that microevolutionary dynamics may alter ecological processes. Rising temperatures under global change are expected to open windows for establishment of species and genotypes from warmer regions. Yet, microevolutionary tracking of temperature change by local populations may reduce establishment success of these immigrants. We exposed a UK population of the water flea, Daphnia magna , to two temperature regimes during a 1.5‐year experimental evolution trial, and subsequently compared competitive strength of non‐warm‐adapted and warm‐adapted D. magna in competition with French genotypes. Our results indicate that local microevolutionary responses to global warming may reduce establishment success of immigrant genotypes that are preadapted to warmer climate. Simulation modeling shows that microevolution results in a reduced likelihood and speed of displacement of local populations by immigrant genotypes under realistic immigrant/resident ratios. We conclude that local evolutionary dynamics may shift the relative impact of local and regional processes in response to global change.

Effects of nutrients and fish on periphyton and plant biomass across a European latitudinal gradient - Eloy Bécares; Joan Gomá; Margarita Fernández-Aláez; Camino Fernández-Aláez; Susana Romo; Maria R. Miracle; Anika Ståhl-Delbanco; Lars-Anders Hansson; Mykael Gyllström; Wouter J. Van de Bund; Ellen Van Donk; Timo Kairesalo; et al. (Aquatic Ecology, 2008)

Shallow lakes, the water framework directive and life. What should it all be about? - Brian Moss (Hydrobiologia, 2007)

Response of macroinvertebrates to warming, nutrient addition and predation in large-scale mesocosm tanks - Heidrun Feuchtmayr; Dermot McKee; Ian F. Harvey; David Atkinson; Brian Moss (Hydrobiologia, 2007)

The art and science of lake restoration - Brian Moss (Hydrobiologia, 2007)

P. E. O’Sullivan and C. S. Reynolds (eds), The Lakes Handbook, Volume 2, Lake Restoration and Rehabilitation - Brian Moss (Journal of Paleolimnology, 2006)

Developmental changes in rat cardiac titin/connectin: transitions in normal animals and in mutants with a delayed pattern of isoform transition - Marion L. Greaser; Paul R. Krzesinski; Chad M. Warren; Brian Kirkpatrick; Kenneth S. Campbell; Richard L. Moss (Journal of Muscle Research and Cell Motility, 2006)

Ecology of Dictyosphaerium pulchellum Wood (Chlorophyta, Chlorococcales) in a shallow, acid, forest lake - Haseeb Md. Irfanullah; Brian Moss (Aquatic Ecology, 2006)

Allelopathy of filamentous green algae - Haseeb Md. Irfanullah; Brian Moss (Hydrobiologia, 2005)

Book Review - Brian Moss (Journal of Paleolimnology, 2004)

Factors controlling hydrochemical and trophic state variables in 86 shallow lakes in Europe - Peeter Nõges; Tiina Nõges; Lea Tuvikene; Halina Smal; Slawomir Ligeza; Ryszard Kornijów; Wojciech Peczula; Eloy Bécares; Francisco Garcia-Criado; Christina Alvarez-Carrera; Camino Fernandez-Alaez; Carmen Ferriol; et al. (Hydrobiologia, 2003)

The structuring role of free-floating versus submerged plants in a subtropical shallow lake - Mariana Meerhoff; Néstor Mazzeo; Brian Moss; Lorena Rodríguez-Gallego (Aquatic Ecology, 2003)

Effects of different fish species and biomass on plankton interactions in a shallow lake - Adrian E. Williams; Brian Moss (Hydrobiologia, 2003)

Abstracts - P. E. Bowden; R. Marks; Christina A. Harrington; Brian Dieckgraefe; Marija Ilčić; Ljiljana Kostović-Knežević; Peter Gruss; Srećko Gajović; Lidija Klampfer; Jorg Cammenga; Stephen Nimer; Sonja Levanat; et al. (Pflügers Archiv - European Journal of Physiology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Ancient blue‐green blooms - Suzanne McGowan; George Britton; Elizabeth Haworth; Brian Moss (Limnology and Oceanography, 1999)
Recent decades have seen a large increase in surface scums (blooms) of cyanophytes (blue‐green algae and blue‐green bacteria) in inland waters. These are potentially toxic to mammals, including humans, and have caused considerable public concern in Europe, Australasia, and North America. They are often associated with eutrophication, and much has been invested in their control. Not all blooms, however, are necessarily the results of human interference with lakes. Scattered paleolimnological evidence indicates that some blooms may be associated with pristine conditions, though this message has largely been ignored. Evidence is given here of a long history of blooms in Whitemere, U.K., from extraction and identification of specific carotenoids from dated sediment cores. Whitemere is representative of a large group of lakes in the West Midlands of the U.K. and is likely to be representative also of those similar postglacial kettle hole lakes in North America and Eurasia, which are groundwater fed with long retention times and thermally stratified. Blue‐green blooms may thus be a normal feature of such lakes and not necessarily a pathology to be controlled.

Ecological challenges for lake management - Brian Moss (Hydrobiologia, 1999)

The effects of tench (Tinca tinca (L.)) and sticklebacks (Gasterosteus aculeatus L.) on planktonic and benthic communities in mesocosms in a shallow lake - Meryem Beklioglu; Brian Moss (Aquatic Ecology, 1998)

The sweet, the salt and the sour: Contrasts in the restoration of aquatic systems - Brian Moss (Aquatic Ecology, 1997)

Vertically-challenged limnology; contrasts between deep and shallow lakes - Brian Moss; Meryem Beklioglu; Laurence Carvalho; Sabri Kilinc; Suzanne McGowan; Deborah Stephen (Hydrobiologia, 1997)

Do rooted macrophytes increase sediment phosphorus release? - Debbie Stephen; Brian Moss; Geoff Phillips (Hydrobiologia, 1997)